Русская литературная усадьба - Новиков Владимир (История. География. Этнография, 2012)
Прим. : с. 243-249 Экземпляры: Аб (20121015) / Инвентарный номер: 98992 / Цена: 288.53 / Сис.шифр: 83.3(2)л6 / Авт.знак: Н 73 / ББК: 83.3(2)л6